Effect of malnutrition at admission on length of hospital stay among adult surgical patients in Wolaita Sodo University Comprehensive Specialized Hospital, South Ethiopia: prospective cohort study - Gebregziabher, Zewdu; Nane, Debritu; Dake, Samson Kastro; Handiso, Yoseph Halala (Frontiers in Nutrition, 2024)
Background Malnutrition in hospitalized patients remains a major public health problem in both developed and developing countries. Even though malnourished patients are more prone to stay longer in hospital, there is limited data regarding the magnitude of malnutrition and its effect on length of stay among surgical in patients in Ethiopia while nutritional assessment is also often a neglected component of the health service practice. Objective This study aims to assess the prevalence of malnutrition at admission and its effect on the length of hospital stay among adult surgical patients in Wolaita Sodo University Comprehensive Specialized Hospital, South Ethiopia, 2022. Methods A facility-based prospective cohort study was conducted among 398 admitted surgical adult patients. Participants in the study were chosen using a convenient sampling technique. Subjective global assessment was used to determine the nutritional status of patients with a minimum stay of 24 h within 48 h after admission (SGA). Data were collected by open data kit (ODK) version 2022.3.3 software while Stata version 14.1 software was employed for statistical analysis. Cox regression model was used to determine the effect of malnutrition on the length of hospital stay (LOS) after adjusted for several potential confounders taken at admission. Adjusted hazard ratio (HR) with 95% confidence interval was used to show the effect of malnutrition. Results The prevalence of hospital malnutrition at admission was 64.32% (95% CI: 59–69%) according to subjective global assessment (SGA) classification. Adult surgical patients who were malnourished at admission had higher median LOS (12 days: 95% CI: 11–13) as compared to well-nourished patients (8 days: 95% CI: 8–9), which means adult surgical patients who were malnourished at admission were at a higher risk of reduced chance of discharge with improvement (prolonged LOS) (AHR: 0.37, 95% CI: 0.29–0.47) as compared to well-nourished patients. The presence of comorbidity (AHR: 0.68, 95% CI: 0.50–90), poly medication (AHR: 0.69, 95% CI: 0.55–0.86), and history of admission (AHR: 0.70, 95% CI: 0.55–0.87) within the previous 5 years were found to be the significant covariates of LOS. Conclusion The magnitude of hospital malnutrition at admission was found to be high. Malnourished patients at admission had a higher risk of prolonged length of hospital stay as compared to well-nourished patients. The presence of comorbidity, poly medication, and history of admission were found to be the significant covariates of LOS. All stakeholders should pay attention to reducing the magnitude of malnutrition and its covariates to improve the burden of LOS.